OP60 Age-friendly environments and physical activity: a cross-sectional, observational study of the over 55s in ireland. (2nd September 2017) - Gibney, S; Ward, M; Sexton, E; Shannon, S
Abstract : Background: The benefits of physical activity extend beyond improving or maintaining physical health. Regular activity reduces the risk of dependency in old age, enables social participation, promotes mental health and well-being, and in combination with other lifestyle factors, may reduce the chances of developing dementia. Despite the benefits of regular physical activity, one-in-three older adults in Ireland have low activity levels. Therefore, the objective of this study is to examine the effect of health, social connectedness, and perceived accessibility and safety of the local environment on physical activity in the over 55 s in Ireland. Methods: Data was from the Age-Friendly City and Counties Survey (2016), a population-representative cross-sectional survey of community-dwelling adults aged 55+administered in 21 Local Authority areas in Ireland (n=10, 540). Data was collected face-to-face using Computer Assistant Personal Interviews. Mixed-effects negative binomial regressions were used to estimate the effect of 1) health status and behaviours, 2) social connectedness, 3) availability and accessibility of recreational green areas, and 4) perceptions of safety in the local area, on physical activity. Moderate and vigorous activity was measured using a brief version of the International Physical Activity Questionnaire and reported as minutes-per-week. Models were adjusted for socio-demographic characteristics. Results are reported as Beta (β) Coefficients, with Standard Errors (S.E). Results: In the fully adjusted model, area-level differences explained 8% of the observed variance in physical activity. Poor health (β −0.74, S.E. 0.22, p<0.001), loneliness (β −0.11, S.E. 0.02, p<0.001), community participation (β 0.34, S.E. 0.5, p<0.001), and difficulty accessing green spaces (β −0.19, S.E. 0.09, p<0.05) partially explained physical activity differences. Several socio-demographic characteristic were also associated with physical activity. Women (β −0.03, S.E. 0.09, p<0.001) older adults (aged 75+) (β −0.02, S.E. 0.07, p<0.001), and those looking after a family or home (β −0.02, S.E. 0.08, p<0.01), were less physically active than their peers. These findings are limited to self-reported perceptions of the local environments whereas geographical data could add further relevant information about area-level social deprivation and distance to services and green spaces. Conclusion: In Ireland, like many other cities and countries that have subscribed to the World Health Organisation's Age-friendly Cities and Counties Programme, locally-directed social and health strategies are increasingly being developed. These results shows that, combined with individual-level behaviour change interventions, improvements to the local environment and promoting social connectedness may be useful in promoting physical activity among the over 55 s.